NUTRITIONAL AND OIL PROFILE OF THE SEEDS OF SESAMUM INDICUM L. AND VITELLARIA PARADOXA C. F. GAERTN. - Ibrahim Umar KARAYE; Sule Aliyu ANKA; Musa Tanko MUHAMMAD; Shafi’u Isma’ila ADILI; Muhammad Hannatu LAWAL (Journal of Plant Development)
Nutritional and oil profile of the seeds of Sesamum indicum and Vitellaria paradoxa from Sokoto, Nigeria was carried out using standard biochemical procedures. Proximate, ascorbic acid, mineral analysis as well as extraction, quantification and the physicochemical analysis of the seed oil were assessed. On proximate and ascorbic acid analysis. The seeds were found to contain appreciable amounts of crude proteins with 18.23% and 8.70% obtained in S. indicum and V. paradoxa respectively. Lipid contents revealed 42.51% in S. indicum and 51.34% in V. paradoxa respectively. Total carbohydrates revealed that 39.03% and 52.12% were obtained in S. indicum and V. paradoxa respectively. Crude fiber contents revealed 5.31 g/100 g in S. indicum while in V. paradoxa, 7.11 g/100 g was recorded. Percentage ash contents revealed 6.62% and 4.61% in S. indicum and V. paradoxa respectively. Available energy (kj) revealed that S. indicum had 603.04 kj/100 g while V. paradoxa had 614.12 kj/100 g respectively signaling them as formidable energy sources. Ascorbic acid analysis revealed 97.36 mg/100 g and 179.16 mg/100 g in S. indicum and V. paradoxa respectively. With significant difference (P=0.05) in the contents of crude proteins, crude lipid, crude carbohydrate, calorific value and ascorbic acid between the two sampled seeds. Minerals analysis revealed that the two seeds were rich in most of the essential minerals required for healthy growth and development. For instance, sodium was found to be 2.67 mg/100 g in S. indicum while 2.23 mg/100 g was identified in V. paradoxa. Potassium, magnesium and phosphorus results indicate that S. indicum had 56.96 mg/100 g, 62.12 mg/100 g and 76.72 mg/100 g and V. paradoxa had 46.72 mg/100 g, 31.64 mg/100 g and 116.74 mg/100 g respectively. With significant difference (P=0.05) in the contents of potassium, magnesium and phosphorus oil extraction and its physicochemical properties revealed that the two seed contained substantial amounts of oil with 38.23% in S. indicum and 43.14% in V. paradoxa respectively. Acid value analysis showed that S. indicum had 32.14 mg KOH/kg while V. paradoxa had 33.24 mg KOH/kg. Saponification value analysis revealed that 131.86 mg KOH in S. indicum while 154.74 mg KOH was found in V. paradoxa. Iodine value analyzed showed that 116.86 g I2 /100 g in S. indicum while 124.77 g I2 /100 g was obtained in V. paradoxa while % Free Fatty Acid analysis revealed that S. indicum had 7.63% while V. paradoxa had 8.74% respectively. With significant difference (P=0.05) between the two species in percentage yield, saponification and iodine values between the two seeds. The two studied seed types are endowed with natural food reserves and other much needed raw materials that could have industrial application making the seeds as formidable ingredients required for use by man.